COMPARISON OF THE EFFECTIVENESS OF ONLINE AND FACE-TO-FACE LEARNING IN IMPROVING CRITICAL THINKING SKILLS - Suriyati (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aims to compare the effectiveness of online and face-to-face learning in improving students' critical thinking skills. The research method used is a quasi-experiment involving two groups of students from high schools. The first group follows online learning, while the second group follows face-to-face learning. Critical thinking skills data were measured using specially designed tests before and after the learning intervention. The results of the analysis showed that both methods had a positive impact on improving students' critical thinking skills. However, the group that followed face-to-face learning showed a more significant increase than the online group. This finding indicates that direct interaction with teachers and peers in face-to-face learning can strengthen students' critical thinking processes. This study concludes that although online learning has advantages in flexibility, face-to-face learning is more effective in improving critical thinking skills. Recommendations for educators include the use of a combination of both methods to maximize learning outcomes and improve students' critical thinking skills in the future.